A hierarchical assembly knowledge representation framework and microdevice assembly ontology. (August 2022) - Zhu, Dongsheng; Zhang, Zhijing; Shi, Lingling; Qian, Jiahui; Qimuge, Saren; Song, Dan
Graphical abstract: Abstract: Microdevice assembly knowledge is dispersed in different product development phases, such as assembly design, assembly simulation and assembly process, and a lot of essential knowledge is implicit and heterogeneous. It is difficult for researchers and computer-aided systems to share and reuse different assembly knowledge quickly and accurately, leading to inefficient and inaccurate assembly process planning. To integrate and structurally represent the assembly design knowledge, assembly simulation knowledge and assembly process knowledge of microdevice, this paper proposes a hierarchical assembly knowledge representation framework and develops a microdevice assembly ontology. There are four layers in the framework, including the organizational structure, the structural relationship, the assembly accuracy, and the process characteristics. The assembly design knowledge that is integrated involves the basic properties of the assembly object as well as the spatial, mating, and assembly relationship, etc. Assembly simulation knowledge refers to the permissible range of assembly force and contact force. Knowledge of assembly processes comprises assembly sequence and operating method of the part. The microdevice assembly ontology is developed based on METHONTOLOGY, and implemented with Protégé. The corresponding SWRL rules have been established to inference the implicit knowledge in assembly design. An ignition target assembly knowledge model based on the microdevice assembly ontology is constructed. In the assembly task of the ignition target, engineers can quickly and accurately access the required assembly knowledge from the ignition target assembly knowledge model, thus verifying the integrity and validity of the microdevice assembly ontology.